Geometric Constructions in the Class of Busemann Nonpositively Curved Spaces - Andreev, P. D. (Журнал математичної фізики, аналізу, геометрії, 2009)
The procedures of gluing and the Hausdorff limit in the class of metric spaces nonpositively curved in the sense of Busemann are studied in the paper. Conditions under which the resulting spaces belong to the same class are found.Mathematics Subject Classification: 53С23.